FRASA BAHASA MELAYU DIALEK KETAPANG - Yulianti, Dina; ., Sukamto; Simanjuntak, Hotma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Penelitian ini bertujuan mendeskripsikan bentuk, fungsi, dan makna frasa Bahasa Melayu dialek Ketapang. Bentuk penelitian kualitatif dengan metode deskriptif. Sumber data dalam penelitian ini yaitu bahasa Melayu dialek Ketapang yang dipakai masyarakat Kelurahan Mulia Kerta. Data dalam penelitian ini berupa frasa bahasa Melayu dialek Ketapang yang didapat melalui wawancara langsung dengan informan yang direkam kemudian diterjemahkan dan dicatat. Dalam pengumpulan data, peneliti menggunakan teknik wawancara, teknik simak libat cakap (SBLC), dan bercerita. Berdasarkan analisis data ditemukan frasa dalam BMDK dapat dibedakan atas (a) frasa endosentris yang meliputi frasa endosentris yang koordinatif, frasa endosentris yang apositif, dan frasa endosentris yang atributif. (b) frasa eksosentris. Bentuk frasa dalam BMDK berdasarkan kategori frasa yaitu frasa nominal, verbal, adjektival, preposisional, dan keterangan. Fungsi frasa dalam kalimat fungsi frasa verbal, adjektival, adverbial, nominal, dan numeralial. Hubungan makna antar unsur-unsur dalam frasa BMDK yakni makna frasa nomina, frasa verba, frasa numeralia, frasa adverbial, dan frasa preposisi. Kata kunci : Bentuk, fungsi, makna frasa dialek Ketapang Â Abstract: this research purpose describe are form, function, and meaning of Malay language in Ketapang dialect. This research is in from of qualitative and descriptive methode. Data source of this research is Malay language in Ketapang dialect thas is spoken by native in Mulia Kerta district. Data in this reseacrh are in from of Malay language in Ketapang dialect that is gained through direct interview with interviewees that is recorder and translated then taken not. In aggregation data, the researcher user interviewing technique, listen and speak technique, and story telling. According to data analysis, it is found that phrase in KDMP can be disringuished into. (a) endocentric phrase that coveos coordinative endocentric, apositive endocentric phrase, and attributive endocentris phrase. (b) exocentrie phrase. Phrase form in KDMP according to phrase categores, they are: nominal phrase, verbal, adjectival, prepositional, and adverbial. Any functions of phrase in senteces, they are functioning as phrasal verb, adjectival phrase, adverbial phrase, nominal phrase, and numeral phrase. Meaning relatioship between elements in phrase KDMP, they are nominal phrase meaning, phrasal verb, numeral phrase, adverbial phrase and prepositional phrase. Keywords: categores, functions, meaning phrase Ketapang dialect